Improvement of Medical Image Near Lossless Coding Algorithm using Grayscale and Bit Plan Matrix - SEDDEQ. E. GHRARE; IBRAHIM A. AKERMI (Surman Journal of Science and Technology, 2024)
Lossless compression techniques can be implemented by entropy coding such as Huffman coding, Differential Huffman coding, Lempel Ziv coding, Run length coding …etc. In this paper, a new near lossless image coding algorithm using different technique will be presented. Our coding algorithm is based on two matrices formulations, which are Gray Scale Matrix (GSM) and Bit Plan Matrix (BPM). Those matrices have been used for encoding and decoding process. As a result, the computational complexity is greatly simplified, therefore producing a very fast coding and encoding processes. This algorithm is most suitable for those images where lossy compression is avoided such as medical images used for teleradiology and telemedicine purposes. Different CT images have been tested. The performance of the proposed algorithm is evaluated using the compression ratio (CR) and peak signal to noise ratio (PSNR). The obtained simulation results showed that a compression ratio of 3.55:1 to 12.15:1 was achieved without affecting the quality of the clinical information.